Flapjacks and feudalism : social mobility and class in The Archers - Courage, Cara; Headlam, Nicola (Emerald Publishing Limited, 2021)
'Flapjacks and Feudalism: Social Mobility and Class in The Archers' is an excavation into the family and class politics found in the clans of the residents of Ambridge, in BBC Radio 4's 'The Archers'. A whole section of the book is devoted to 'The Fall of the House of Aldridge', with Brian's ethical misdemeanours and fall from grace, looking at how Brian could have hidden his scandals and changed the impressions surrounding him as a 'feckless farmer'. Another section sees the parenting skills, or complete lack of them, of the Ambridge clans put on trial, and used to predict the future leaders of Ambridge. Chapters in the book discuss the power of family and community networks, the oppression of the Grundys by the lords of the manor, and Emma Grundy's housing woes and the importance of housing in the success and security of those in the village. This book explores how far housing, intergenerational wealth, skills and access to employment shape life chances of characters and shows that, perhaps more than anywhere else, its not what you know but who you know.